2020
DOI: 10.24018/ejmed.2020.2.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification And Prevalence Of Pseudomonas Aeruginosa Isolates From Clinical And Environmental Sources In Onitsha Metropolis, Anambra State

Abstract: This study was aimed to isolate and identify Pseudomonas aeruginosa and to determine the prevalence rate of isolated P. aeruginosa in Hospitals in Onitsha. Isolates of P. aeruginosa were recovered from both clinical and environmental sources using Cetrimide agar, Blood agar, Mueller-Hinton agar and MacConkey agar.  All the inoculated plates were incubated at 37°C for 24-48 hours and growth was evaluated on these media. Isolates were identified on the basis of standard bacteriological methods like morphology, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…Interviews with the locals in our study area revealed that ciprofloxacin was a commonly used antibiotic within that area (data not shown). Strikingly, we observed a 75% resistance to ciprofloxacin, which was comparably higher than the 22.9% and 45.5% reported by earlier studies in Pakistan 26 and South-Eastern Nigeria 21 respectively. Single therapy from health care practitioners, or selective pressure arising from frequent use, may be responsible for the emergence of resistance to this broad-spectrum antibiotic 27 Previously, we had reported a 50% resistance to nitrofurantoin by Pseudomonas spp., isolated from smoked fish in Dutsinma, Katsina State, Nigeria.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Interviews with the locals in our study area revealed that ciprofloxacin was a commonly used antibiotic within that area (data not shown). Strikingly, we observed a 75% resistance to ciprofloxacin, which was comparably higher than the 22.9% and 45.5% reported by earlier studies in Pakistan 26 and South-Eastern Nigeria 21 respectively. Single therapy from health care practitioners, or selective pressure arising from frequent use, may be responsible for the emergence of resistance to this broad-spectrum antibiotic 27 Previously, we had reported a 50% resistance to nitrofurantoin by Pseudomonas spp., isolated from smoked fish in Dutsinma, Katsina State, Nigeria.…”
Section: Discussioncontrasting
confidence: 71%
“…The high resistance to cefuroxime (100%) and ceftazidime (95%) observed from Kadangaru and Miami respectively ( Table 3 ), corroborates a 100% resistance to the same antibiotics reported in an earlier study carried out in Onitsha, Nigeria. 21 The resistance to cephalosporins observed in this study portends serious public health concerns, especially with the rising emergence of resistance to this group of antibiotics. 24 The unrestricted usage of these antibiotics in our study area is probable for the high resistance to cephalosporin we observed.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Pseudomonas aeruginosa is a Gram-negative facultatively anaerobic straight or slightly curved rod 1 to 3μm long and 0.5 to 1.0μm wide that produces one or more water soluble pigments including pyoverdine a yellow-green fluorescent pigment, pyorubin a redbrown pigment, pyocyanin a blue-green pigment, and pyomelanin a dark pigment (Ezeador et al, 2020). It is an opportunistic pathogen and member of the ESKAPE group of pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter species) notorious for being highly virulent and resistant to antibiotics.…”
mentioning
confidence: 99%